Technical Note: Novel Use of CytoSorb™ Haemadsorption to Provide Wound Healing Support in Case of Severe Burn Trauma via Reduction of Hyperbilirubinaemia - Rachunek, Katarzyna; Krause, Maja; Thiel, Johannes Tobias; Kolbenschlag, Jonas; Daigeler, Adrien; Bury, Andreas (Frontiers in Surgery, 2021)
Hyperbilirubinaemia has been shown to compromise wound healing in severely burned patients. The therapy options for patients with impairment of wound healing and subsequent severe liver dysfunction are limited. A novel extracorporeal treatment, CytoSorb® (CytoSorbents Corp, USA), is a whole blood adsorber composed of highly biocompatible and porous polystyrene divinylbenzene copolymer beads covered in a polyvinylpyrrolidone coating. It is capable of extracting mainly hydrophobic middle-sized (up to 55 kDa) molecules from blood via size exclusion, including cytokines and bilirubin. We performed therapy with CytoSorb® on a severely burned (48% Total Body Surface Area - TBSA) patient with secondary sclerosing cholangitis (SCC) to promote the wound healing process by reducing bilirubin concentrations and to bridge the time to spontaneous liver regeneration or eventually to liver transplantation after two skin transplantations had failed to provide wound closure. In the first 6 days the cartridge was changed on a daily basis and later after every 2–4 days. The therapy with 6 adsorbers decreased a total bilirubin concentration from 14.02 to 4.29 mg/dl. By maintaining a stable bilirubin concentration under 5 mg/dl, debridement of abdomen and upper extremities with autologous skin grafting and, 4 weeks later, autologous skin grafting of the back from scrotum and lower extremities were performed successfully. After wound healing had been achieved, the CytoSorb therapy was discontinued after 57 days and 27 adsorber changes. CytoSorb therapy can be a promising support of wound and skin graft healing in patients with severe burns and liver dysfunction due to a significant reduction of total bilirubin concentration.